2018
DOI: 10.1186/s41232-018-0089-2
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 in skin biology: new insights from gene-manipulated mice and lipidomics

Abstract: The skin represents one of the tissues that are most profoundly influenced by alterations in the quality of lipids (lipoquality). Lipids not only constitute cellular membranes, but also serve as bioactive lipid mediators and essential components of the skin barrier. Phospholipase A2 (PLA2) enzymes supply fatty acids and lysophospholipids from membrane phospholipids, thereby variably affecting cutaneous homeostasis. Accordingly, perturbation of particular PLA2-driven lipid pathways can be linked to various form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Interestingly, the inhibition of cPLA 2 ɑ (rows 4-6) mainly affects proliferation markers and only some inflammatory and immune cell markers. These results agree with previous studies of the role of PLA2 enzymes and their downstream products in psoriasis (Ashcroft et al , 2020) and skin biology in general (Murakami et al , 2018). Moreover, it is worth noting that the targeting of cPLA 2 ɑ appears to mainly act on the Th17 cell-related markers, but not on the Th1 markers.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the inhibition of cPLA 2 ɑ (rows 4-6) mainly affects proliferation markers and only some inflammatory and immune cell markers. These results agree with previous studies of the role of PLA2 enzymes and their downstream products in psoriasis (Ashcroft et al , 2020) and skin biology in general (Murakami et al , 2018). Moreover, it is worth noting that the targeting of cPLA 2 ɑ appears to mainly act on the Th17 cell-related markers, but not on the Th1 markers.…”
Section: Resultssupporting
confidence: 93%
“…The PLA2 family is a major regulator of lipid metabolism ( 20 ). To determine the immune regulatory roles of PLA2-regulated lipids in psoriasis, we first performed liquid or gas chromatography–mass spectrometry (LC/GC-MS) analysis of phospholipids and eicosanoids in normal (NC), nonlesional, and psoriatic skin (PV).…”
Section: Resultsmentioning
confidence: 99%
“…The PLA2G2F, PLA2G4D, and PLA2G4E enzymes are part of the phospholipase A2 family, which has over 30 members, consisting of both cytosolic PLA2s (such as PLA2G4D and PLA2G4E), and secreted PLA2s (i.e., PLA2G2F), with variable expression of different members in a broad range of tissues (11,20). Studies have demonstrated that PLA2 enzymes regulate lipid pathways, and that many of these lipid species generated by these enzymes serve as bioactive mediators and essential components of the skin barrier (20,27). In addition, individual PLA2 enzymes exhibit unique tissue and cellular distribution, suggesting that they have distinct biological roles in production of pro-and anti-inflammatory lipid mediators (20,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our report of differential expression of these genes for at least three days after initiation of TE indicates that it may be valuable to investigate their role in the mechanotransduction process. Of notable interest are genes SFRP2, which enhances the osteogenic differentiation of apical papilla stem cells by antagonizing the canonical WNT pathway 41 , and PLA2G2F, which regulates skin homeostasis and keratinocyte differentiation 42,43 . Additional genes include SPPI, which is involved in post-injury tissue remodeling in mice 44 , and SAA3, which regulates collagenase expression an in vitro in rabbit fibroblast, substantiating their roles in tissue remodeling 45 .…”
Section: Discussionmentioning
confidence: 99%